1990
DOI: 10.1159/000117171
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter and Receptor Alterations in the Rat Persistent Dyskinesia Model Induced by Iminodipropionitrile

Abstract: Chronic administration of iminodipropionitrile (IDPN), a neurotoxin, to rats produces a persistent behavioral syndrome characterized by lateral and vertical head twitching, random circling and hyperactivity. Conventionally, this IDPN-induced dyskinesia has been considered to be due to abnormalities in the serotonin neuronal system. However, the present study also demonstrated marked alterations in the dopamine (DA) and acetylcholine (ACh) neuronal systems. These were activation of DA neurons in the nucleus acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The IDPN-induced dyskinesia was considered due to activation of DA neurons and enhanced by administration of L-dopa, which increases DA concentration. Moreover, hyperfunction of DA neuronal system could be relieved by Tia [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The IDPN-induced dyskinesia was considered due to activation of DA neurons and enhanced by administration of L-dopa, which increases DA concentration. Moreover, hyperfunction of DA neuronal system could be relieved by Tia [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The increase of DA is inhibited by sulpiride, a central antagonist of D2R. Therefore, dyskinesia of DA is caused by the abnormally enhanced function of presynaptic DA neurons (Ogawa et al, 1990). IDPN only needs to be injected intraperitoneally, which makes it easy to prepare and utilize, so we used IDPN to induce a model of TS in mice.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the effect of bromocriptine was due to stimulation of postsynaptic D 2 -receptors in the striatum and that there was a significant equilibration delay in the concentrations in the brain compared to those in plasma. The onset and duration of the effects of bromocriptine have been described in previous reports (Corrodi et al, 1973;Johnson et al, 1976;Schran et al, 1985;Ogawa et al, 1990). Corrodi et al (1973) reported that bromocriptine induced rotation in rats with 6-OHDA-induced lesions with a delay of 50 -60 min after administration, whereas ergocornine-induced rotation commenced within 5 min.…”
Section: Discussionmentioning
confidence: 76%
“…Johnson et al (1976) also reported that bromocriptine exhibited a time delay in the onset of effects such as stereotyped sniffing-licking and contralateral rotation in 6-OHDA-lesioned rats and that the drug had a sustained action in contrast to the actions of apomorphine, amphetamine, and L-dopa. Moreover, the duration of the effect in rats of bromocriptine has been studied with respect to suppression of iminodipropionitrail-induced head twitching (Ogawa et al, 1990) and bromocriptine-induced hypothermia (Schran et al, 1985). In some cases, active metabolites may cause a delay in the onset of the effect of a drug compared to plasma concentration.…”
Section: Discussionmentioning
confidence: 99%